Effectiveness of a Smoking Cessation Program Applying Participatory Learning on Behavior Change for High School Students in Chiang Mai Province - Punpom, Duanchay; Moolphate, Saiyud; Khomchai, Songyos (Academic Psychiatry and Psychology Journal, 2018)
Abstract Objectives: To study the effectiveness of participatory learning on behavior change for smoking cessation among grade 10-12 students. Materials and Methods: This was a one group pretest-posttest quasi experimental study. 31 students from grades 10-12 aged 15-18 years who smoked were recruited for the study. The participatory learning techniques, the stages of change theory and self-efficacy were applied to this study. The duration of participatory learning intervention was 8 weeks with total of 16 sessions organized two times per week from November 2015 – December 2016. Data were collected by using questionnaires and the measurement of carbon monoxide by piCO+Smokerlyzer®. The data was analyzed by a percentage, mean, Standard Deviation Repeated Measures ANOVA and the Wilcoxon signed - rank test. Findings: 18 students (58.10%) were successful in stop smoking. Knowledge and motivation for smoking cessation increased compared to the baseline. The self-report of cigarettes per day and the mean of carbon monoxide by piCO+Smokerlyzer® were lower than the baseline measurement. (P<0.001). Conclusions: The participatory learning technique may be able to change smoking cessation behaviors in students. KEYWORDS : Smoking, Participatory learning, Behavior change, Smoking cessation. ประสิทธิผลของการเรียนรู้แบบมีส่วนร่วมต่อการปรับเปลี่ยนพฤติกรรมการเลิกสูบบุหรี่ ของนักเรียนชั้นมัธยมศึกษาตอนปลาย จังหวัดเชียงใหม่ บทคัดย่อ วัตถุประสงค์ เพื่อศึกษาประสิทธิผลของการจัดกิจกรรมการเรียนรู้แบบมีส่วนร่วมต่อการปรับเปลี่ยนพฤติกรรมการเลิกสูบบุหรี่ของนักเรียนชั้นมัธยมศึกษาตอนปลาย วัสดุและวิธีการ เป็นการวิจัยกึ่งทดลองแบบกลุ่มเดียววัดผลก่อนและหลังการจัดกิจกรรม (One group Pretest-Posttest Quasi Experimental Design) กลุ่มตัวอย่าง คือ นักเรียนชั้นมัธยมศึกษาตอนปลาย โรงเรียนแห่งหนึ่งในอำเภอดอยหล่อ จังหวัดเชียงใหม่ ที่มีพฤติกรรมการสูบบุหรี่ จำนวน 31 คน โดยประยุกต์แนวคิดทฤษฎีขั้นตอนการเปลี่ยนแปลงพฤติกรรม ร่วมกับการรับรู้ความสามารถของตนเอง มากำหนดกิจกรรมการเรียนรู้แบบมีส่วนร่วม จำนวน 8 สัปดาห์ๆ ละ 2 ครั้ง รวมทั้งสิ้น 16 ครั้ง ตั้งแต่เดือนพฤศจิกายน 2558 ถึงเดือนมกราคม 2559 เก็บรวบรวมข้อมูลด้วยแบบสอบถาม และเครื่องตรวจวัดก๊าซคาร์บอนมอนอกไซด์ในลมหายใจ (piCO+Smokerlyzer®) วิเคราะห์ข้อมูลด้วยสถิติร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน การวิเคราะห์ความแปรปรวนเมื่อมีการวัดซ้ำและการทดสอบวิลคอกซัน ผลการศึกษา หลังกิจกรรมฯนักเรียนสามารถเลิกสูบบุหรี่ได้ จำนวน 18 คน คิดเป็นร้อยละ 58.10 ความรู้เกี่ยวกับพิษภัยของบุหรี่และการเลิกสูบบุหรี่ รวมทั้งแรงจูงใจในการเลิกสูบบุหรี่ (P<0.001)เพิ่มขึ้น และค่าเฉลี่ยมวนบุหรี่ที่สูบต่อวันและค่าเฉลี่ยก๊าซคาร์บอนมอนอกไซด์ในลมหายใจลดลง (P<0.001) สรุป การใช้กิจกรรมการเรียนรู้แบบมีส่วนร่วม อาจปรับเปลี่ยนพฤติกรรมการเลิกสูบบุหรี่ของนักเรียนได้ คำสำคัญ : การเรียนรู้แบบมีส่วนร่วม, การปรับเปลี่ยนพฤติกรรม, การเลิกสูบบุหรี่